Killing me softly - Programmed cell death in plant reproduction from sporogenesis to fertilization. (October 2022) - Xie, Fei; Vahldick, Hannah; Lin, Zongcheng; Nowack, Moritz K.
Abstract: Regulated or programmed cell death (RCD or PCD) is a fundamental biological principle integral to a considerable variety of functions in multicellular organisms. In plants, different PCD processes are part of biotic and abiotic stress responses, but also occur as an essential aspect of unperturbed plant development. PCD is particularly abundant during plant reproduction, eliminating unwanted or no longer needed cells, tissues, or organs in a precisely controlled manner. Failure in reproductive PCD can have detrimental consequences for plant reproduction. Here we shed a light on the latest research into PCD mechanisms in plant reproduction from sex determination over sporogenesis to pollination and fertilization.